Frequency effects in the dynamic lateral stiffness of monopiles in sand: insight from field tests and 3D FE modelling. Issue 9 (31st July 2020) - Kementzetzidis, Evangelos; Metrikine, Andrei V.; Versteijlen, Willem G.; Pisanò, Federico
Abstract : With the offshore wind industry rapidly expanding worldwide, geotechnical research is being devoted to foundation optimisation – most intensively for large-diameter monopiles. The analysis and design of monopiles still suffers from significant uncertainties in relation to cyclic/dynamic loading conditions. The aim of this work is to shed new light on dynamic soil–monopile interaction, based on the results of unique full-scale experiments performed at the Westermeerwind wind park (Netherlands). The response of a 24 m long, 5 m diameter monopile to harmonic lateral loading of varying amplitude and frequency is inspected. The analysis of original field measurements (soil accelerations and pore pressures) enables the lateral stiffness observed at the monopile head to be linked to dynamic effects occurring in the surrounding soil. The interpretation of measured data is supported by three-dimensional finite-element studies, also looking at the influence of drainage conditions and monopile size. The set of results presented supports the need for dynamics-based monopile design, as higher frequencies gain relevance in the most recent offshore wind developments.